2017
DOI: 10.1186/s11671-017-1965-4
|View full text |Cite
|
Sign up to set email alerts
|

Au Gratings Fabricated by Interference Lithography for Experimental Study of Localized and Propagating Surface Plasmons

Abstract: Optical properties of high-frequency Au gratings with a fixed period (296.6 ± 0.5 nm) and a variable modulation depth are studied using measurements of spectral and angular dependence of transmission and reflection of polarized light in order to build the dispersion curves of excited optical modes and to identify their types. It was shown that in gratings with small modulation depth only propagating surface plasmon-polaritons (SPP) modes were observed. With increasing of modulation depth, the intensity of SPP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 16 publications
1
16
0
Order By: Relevance
“…But this weak dependence of the resonance spectral position is characteristic for the LP excitation in a periodic array of nanowires [6]. This result agrees with the previous measurements, where it was shown that only local plasmons are excited in the grating of isolated nanowires, when slits between nanowires are wider than the half-period of the grating nanowires are wider than the half-period of the grating [10]. At the same time, no extinction bands are observed in S-polarization at φ = 0.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…But this weak dependence of the resonance spectral position is characteristic for the LP excitation in a periodic array of nanowires [6]. This result agrees with the previous measurements, where it was shown that only local plasmons are excited in the grating of isolated nanowires, when slits between nanowires are wider than the half-period of the grating nanowires are wider than the half-period of the grating [10]. At the same time, no extinction bands are observed in S-polarization at φ = 0.…”
Section: Resultssupporting
confidence: 92%
“…So, for large distances between nanowires the influence of LP-SPP interaction is not essential, and we observe only the LP peak. However, when the slit width between grating grooves decreases, the optical response of the grating may change [10]. Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Amorphous AsSe based semiconductor chalcogenide glasses (ChG) have a number of properties that allow their applications as positive and negative optical and electronic resists as well as for direct relief formation due to photo-fluidity and mass-transport phenomena [25,26]. We have shown their unique sensitivity for localized plasmon fields and perspectives of plasmon-assisted nanolithography, a near-field nanoimaging [27] as well as to plasmonic structures productions [28]. Thus, using ChG as a nanolithography mask material provides opportunities for a combination of different types of lithographic patterning.…”
Section: Introductionmentioning
confidence: 99%